WHIM syndrome caused by a single amino acid substitution in the carboxy-tail of chemokine receptor CXCR4 - Liu, Qian (American Society of Hematology, 2012)
WHIM syndrome is a rare, autosomal dominant, immunodeficiency disorder so-named because it is characterized by warts, hypogammaglobulinemia, infections, and myelokathexis (defective neutrophil egress from the BM). Gain-of-function mutations that truncate the C-terminus of the chemokine receptor CXCR4 by 10-19 amino acids cause WHIM syndrome. We have identified a family with autosomal dominant inheritance of WHIM syndrome that is caused by a missense mutation in CXCR4, E343K (1027G → A). This mutation is also located in the C-terminal domain, a region responsible for negative regulation of the receptor. Accordingly, like CXCR4(R334X), the most common truncation mutation in WHIM syndrome, CXCR4(E343K) mediated approximately 2-fold increased signaling in calcium flux and chemotaxis assays relative to wild-type CXCR4; however, CXCR4(E343K) had a reduced effect on blocking normal receptor down-regulation from the cell surface. Therefore, in addition to truncating mutations in the C-terminal domain of CXCR4, WHIM syndrome may be caused by a single charge-changing amino acid substitution in this domain, E343K, that results in increased receptor signaling.